PRODUKTIVITAS RATUN SORGUM VARIETAS KAWALI DENGAN PEMUPUKAN BOKASHI FESES SAPI - Agnitje Rumambi; Malky Telleng; Wilhelmina Kaunang; Sjeny Malalantang (Udayana University, 2018)
This study aims to determine the effect of bokashi cow feces on the productivity of ratoon sorghum variety of kawali. This research design used was completely randomized design (CRD), which consists of 4 treatments and 5 replications. The treatment consists of P0= without fertilization, P1= 4 kg of fertilization, P2= 8 kg of fertilization, P3= 12 kg of fertilization. The measured variables are number of tillers, plant height, and panicle weight. Result of the analysis showed that treatment with 12 kg/plot provides highly significant effect (P <0.01) of the number of tillers, plant height, and panicle weight compared without fertilization, 4 and 8 kg/plot fertilization. Based on this research it can be concluded that cattle feces bokashi as the organic fertilizer up to 12 kg produced the best effect on number of tillers, plant height, and panicle weight. Ratoon harvest yields plant height 16,65% and panicle weight 2,65% higher than first harvest. Keywords: Bokashi, kawali productivity, ratoon, sorghum